2007
DOI: 10.1177/021849230701500626
|View full text |Cite
|
Sign up to set email alerts
|

Acute Fatal Post-CABG Low Dose Amiodarone Lung Toxicity

Abstract: Amiodarone is one of the commonly used anti-arrhythmic agents with well-recognized chronic pulmonary toxicity. We present our experience of a patient with a fatal outcome after coronary artery bypass grafting and a short course of amiodarone treatment with a low total cumulative dose for the treatment of postoperative atrial fibrillation. Necropsy revealed diffuse pulmonary damage due to acute amiodarone lung toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
1
2
0
1
Order By: Relevance
“…In our study, we found shorter clinical onset and more severe hypoxemia in non-surviving patients. This has been observed in cardiac surgery with the use of intravenous amiodarone for the prevention of perioperative arrhythmia [2,18]. This observation could support the hypothesis of an allergic immune reaction against amiodarone or its metabolites during severe APT.…”
Section: Discussionsupporting
confidence: 63%
“…In our study, we found shorter clinical onset and more severe hypoxemia in non-surviving patients. This has been observed in cardiac surgery with the use of intravenous amiodarone for the prevention of perioperative arrhythmia [2,18]. This observation could support the hypothesis of an allergic immune reaction against amiodarone or its metabolites during severe APT.…”
Section: Discussionsupporting
confidence: 63%
“…49 According to some authors, lung toxicity is more likely to occur in ICU patients in which the oxidative damage of high oxygen partial pressure potentiates the free radicals derived from the iodine accumulated in the alveoli. 50 However, it worth highlighting that acute lung toxicity is an adverse event reported anecdotally; 51,52 rather a cumulative dose of 150 grams, 400 mg daily for three months or 200 mg for more than eighteen months are associated with pulmonary injury. 53,54,5556 On the contrary, liver toxicity requires as high as 300 grams of cumulative dose, 57 but according to some German scholars, one third of the SARS-CoV-2 patients admitted in ICU has shock liver, which may compromise amiodarone metabolism.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…16,17 Surrogate endpoints of pulmonary complications from our STS database suggest no statistical difference in pulmonary outcomes in the amiodarone group (Table 2). Two large meta-analyses add further evidence for the safety of postoperative amiodarone.…”
Section: Commentsmentioning
confidence: 99%